Urine manipulation with liquid soap: A case report. Issue 5 (25th February 2020) - Gmeiner, Günter; Geisendorfer, Thomas
Abstract: Among the various strategies to enhance performance by the use of doping substances or methods, sample manipulation to cheat common detection strategies is prohibited by the World Antidoping Agency. Two cases of urine sample adulteration with surfactants are presented in this article, as well as an easy strategy for the detection of this sort of sample manipulation. Abstract : Among the various strategies to enhance performance by the use of doping substances or methods, sample manipulation to cheat common detection strategies is prohibited by the World Antidoping Agency. Two cases of urine sample adulteration with surfactants are presented in this article as well as an easy strategy for the detection of this sort of sample manipulation.